2011
DOI: 10.1164/rccm.201001-0115oc
|View full text |Cite
|
Sign up to set email alerts
|

Written Action Plan in Pediatric Emergency Room Improves Asthma Prescribing, Adherence, and Control

Abstract: Provision of a written action plan significantly increased patient adherence to inhaled and oral corticosteroids and asthma control and physicians' recommendation for maintenance fluticasone and medical follow-up, supporting its independent value in the acute-care setting. Clinical trial registered with www.clinicaltrials.gov (NCT 00381355).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 52 publications
7
123
0
4
Order By: Relevance
“…A trial conducted with 219 children with asthma treated in the ED demonstrated that the WAAP group was more likely to adhere to inhaled corticosteroids, fill oral corticosteroid prescriptions, and report better asthma control at 28 days postdischarge (26).…”
Section: Discussionmentioning
confidence: 99%
“…A trial conducted with 219 children with asthma treated in the ED demonstrated that the WAAP group was more likely to adhere to inhaled corticosteroids, fill oral corticosteroid prescriptions, and report better asthma control at 28 days postdischarge (26).…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] No Brasil, estima-se que haja cerca de 20 milhões de asmáticos, considerando-se uma prevalência de 10%. 7 Nos Estados Unidos, a asma afeta cerca de 5 milhões de crianças.…”
Section: 4unclassified
“…9 Observa-se que, se por um lado, a incidência da asma está aumentando, por outro, não ocorre o mesmo com a adesão às diretrizes nacionais de diagnóstico e tratamento. 2,10 A asma é uma doença crônica frequente na infância, que requer esforços coordenados por crianças, famílias e profissionais de saúde para o controle e tratamento adequados. 3 As orientações clínicas práticas recomendam que os médicos ofereçam educação sobre asma para pacientes e suas famílias.…”
Section: 4unclassified
See 1 more Smart Citation
“…If it was inadequate, review the action plan and provide written guidance to assist if asthma worsens again. 402,403 • Review the patient's use of controller treatment before and during the exacerbation. Was it increased promptly and by how much?…”
mentioning
confidence: 99%